Factors Influencing Anesthesiologists in Conducting Pre-Anesthesia Assessments on Surgical Patients with Cardiovascular Disorders - Putu Atika Parwati; Ni Luh Putu Lusiana Devi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pre-anesthesia assessment is very important in ensuring the success of surgical procedures, especially in cases involving comorbidities, such as cardiovascular disorders. Pre-anesthesia assessment is often only performed by 19.5% of anesthesiologists, and the results are not recorded immediately after the procedure in the patient's medical records due to time constraints. This study aims to determine the factors that influence anesthesiologists in conducting pre-anesthesia assessments on surgical patients with cardiovascular disorders. The research design used was a correlational analytical study with a cross-sectional approach. The population was anesthetists in Indonesia, and the sample was selected using purposive sampling. Univariate analysis was performed by determining the frequency distribution and percentage of general characteristics of respondents, while bivariate analysis with chi-square was performed to determine the relationship between factors affecting anesthetists in conducting pre-anesthesia assessment on surgical patients with cardiovascular disorders. The sample size in this study was 245 respondents. The results of the study showed that factors associated with the implementation of pre-anesthesia assessment in surgical patients with cardiovascular disorders were length of service (p 0.020), workload (p 0.018), and number of anesthesiologists (p 0.009).